Parental Belief dan Self-Esteem Anak: Studi pada Budaya Betawi - Sally Carolina; Sri Hartati R Suradijono (Provitae: Jurnal Psikologi Pendidikan, 2019)
Self-esteem is one aspect that can affect the mental development of children and will further affect the well-being of individuals. One of the factors that can influence is parenting from parents. Parental belief is one of the factors that play a role to underlie the behavior of parents to children. This study aims to see the picture of the dimensions that on parental belief variable, that is child rearing of belief scale, attribute of intelligence, and educational goals, as well as its influence on the development of self-esteem in elementary school-age children, especially in grade 3, 4 and 5 elementary school children on the people of the Betawi culture. Betawi culture is used as a special context in this study because it has unique characteristics when compared to other cultures in Indonesia. The number of participants included in this study were 36 participants spread across several areas of Jakarta. The parental belief in Betawi culture according to the dimensions in PBQ is obtained in the dimensions of the child rearing belief scale, the highest subdimension is developing practical skills; on the dimensions of attributes of intelligence, the highest subdimension is motivation for school tasks; and on the dimensions of the educational goals, the highest subdimension is emphasize conformity. To see the effect of dimensions on parental belief in self esteem, researchers use multiple regression methods. The results obtained there were no significant effects of each dimension of parental belief in children self-esteem.